Assessing the Impact of Suboptimal Donor Characteristics on Mortality After Liver Transplantation: A Time-dependent Analysis Comparing HCC With Non-HCC Patients. Issue 4 (April 2019) - Wallace, David; Walker, Kate; Charman, Susan; Suddle, Abid; Gimson, Alex; Rowe, Ian; Callaghan, Chris; Cowling, Tom; Heaton, Nigel; van der Meulen, Jan
Abstract : Background: Patients who receive a liver transplant for hepatocellular carcinoma (HCC) often receive poorer-quality livers. Tumor recurrence also has a negative effect on posttransplant outcomes. We compared mortality of HCC and non-HCC recipients in different posttransplant time periods (epochs) to separate the impact of these different risk factors on short-term and longer-term posttransplant survival. Methods: We identified a population-based cohort of first-time liver transplant recipients (aged ≥16 years) between 2008 and 2016 in the United Kingdom. We used Cox regression to estimate hazard ratios (HRs) comparing posttransplant mortality between HCC and non-HCC patients in 3 posttransplant epochs: 0 to 90 days, 90 days to 2 years, and 2 to 5 years, with adjustment first for recipient and later also for donor characteristics. Results: One thousand two hundred seventy HCC and 3657 non-HCC transplant recipients were included. Five-year posttransplant survival was 74.5% (95% confidence interval [CI] 71.2%–77.5%) in HCC patients and 84.6% (83.0%–86.1%) in non-HCC patients. With adjustment for recipient characteristics only, mortality of HCC patients was lower but not statistically significantly different in the first 90 days (HR, 0.76; 95% CI, 0.53–1.09; P = 0.11), but significantly higher thereafter (90 days to 2 years: HR, 1.99; 95% CI, 1.48–2.66; P < 0.001; 2 to 5 years HR, 1.77; 95% CI, 1.30–2.42; P < 0.001). Further adjustment for donor characteristics had little impact on these results. Conclusions: HCC recipients have poorer 5-year posttransplant survival than non-HCC recipients, most likely because of tumor recurrence. The more frequent use of poorer-quality donor organs for HCC does not explain this difference. Abstract : Supplemental Digital Content is available in the text.